Use of conversational silence by Malaysian science and non-science undergraduate students in academic discourse - Ibrahim, Bashir (2017)
In the last few decades, there has been a renewed interest in the study of silence as a linguistic tool used by humans for communication purposes. Many past researchers on the use of silence, however, concentrated on studying silence in the classroom context. Few studies, if at all available, are on conversational silence in academic discourse. Still, there is paucity of research on the effect of task types or students’ field of study on the use of conversational silence. This study sought to investigate the perceptions of Malaysian undergraduates on the use of conversational silence in academic discourse. It examined its use by two distinct groups of Malaysian students - science and non-science - in their academic interactions. It also determined the extent to which different academic task types affect the use of conversational silence by the two groups. In addition, it explored how culture plays a role in the use of conversational silence, and identified factors that contribute to its use by the groups. Multiple instruments such as observations, focus group interviews, focus group discussions and video/audio recordings were used as tools for data collection. The study was underpinned by Sacks, Shegloff and Jefferson’s (1974) Turn-taking theory, and Austin (1967) and Seale’s (1969) Speech Act Theory. Conversation analysis using Drew and Heritage (1992) transcription notations and content analysis were used to analyze the data. The conversation analysis mainly concentrated on the analysis of types of silence – gap, lapse, pause, interruption and overlap during conversation, while content analysis was used to analyze the interview data. Content analysis, therefore, has helped determine how culture plays a role in the use of silence, and explore factors which influence the use of silence. The overall result of the focus group interview indicated that the use of silence depends on the context, situation, and the participants involved. The result of the use of silence in academic discourse tended to indicate that both science and non-science participants of this study were similar in their use of silence, probably due to the similarity of their socio-cultural background. The findings suggest that where students share similar socio-cultural upbringing, their use of silence tends to be similar irrespective of their field of study. The nature of academic activity, however, may affect their use of silence. Future studies may consider the use of silence in ‘authentic’ academic situations such as during seminars or workshops, and among students at various levels of education.